DNA methylation in Cosmc promoter region and aberrantly glycosylated IgA1 associated with pediatric IgA nephropathy. - Qiang Sun; Jianqian Zhang; Nan Zhou; Xiaorong Liu; Ying Shen (PLoS ONE)
IgA nephropathy (IgAN) is one of the most common glomerular diseases leading to end-stage renal failure. Elevation of aberrantly glycosylated IgA1 is a key feature of it. The expression of the specific molecular chaperone of core1ß1, 3galactosyl transferase (Cosmc) is known to be reduced in IgAN. We aimed to investigate whether the methylation of CpG islands of Cosmc gene promoter region could act as a possible mechanism responsible for down-regulation of Cosmc and related higher secretion of aberrantly glycosylated IgA1in lymphocytes from children with IgA nephropathy. Three groups were included: IgAN children (n = 26), other renal diseases (n = 11) and healthy children (n = 13). B-lymphocytes were isolated and cultured, treated or not with IL-4 or 5-Aza-2'-deoxycytidine (AZA). The levels of DNA methylation of Cosmc promotor region were not significantly different between the lymphocytes of the three children populations (P = 0.113), but there were significant differences between IgAN lymphocytes and lymphocytes of the other two children populations after IL-4 (P<0.0001) or AZA (P<0.0001). Cosmc mRNA expression was low in IgAN lymphocytes compared to the other two groups (P<0.0001). The level of aberrantly glycosylated IgA1 was markedly higher in IgAN group compared to the other groups (P<0.0001). After treatment with IL-4, the levels of Cosmc DNA methylation and aberrantly glycosylated IgA1 in IgAN lymphocytes were remarkably higher than the other two groups (P<0.0001) with more markedly decreased Cosmc mRNA content (P<0.0001). After treatment with AZA, the levels in IgAN lymphocytes were decreased, but was still remarkably higher than the other two groups (P<0.0001), while Cosmc mRNA content in IgAN lymphocytes were more markedly increased than the other two groups (P<0.0001). The alteration of DNA methylation by IL-4 or AZA specifically correlates in IgAN lymphocytes with alterations in Cosmc mRNA expression and with the level of aberrantly glycosylated IgA1 (r = -0.948, r = 0. 707). Our results suggested that hypermethylation of Cosmc promoter region could be a key mechanism for the reduction of Cosmc mRNA expression in IgAN lymphocytes with associated increase in aberrantly glycosylated IgA1.